2013
DOI: 10.1136/neurintsurg-2012-010607.rep
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic warning of hemorrhagic transformation after stent retriever thrombectomy procedure

Abstract: SUMMARYThis study reports cerebral angiographic findings observed after stent retriever thrombectomy that is suggestive of a higher risk of hemorrhagic transformation (HT). A woman aged 65-75 presented with a right middle cerebral artery syndrome confirmed by non-contrast CT brain scan. Endovascular revascularization using the Solitaire device was placed across the thromboembolic occlusion and thromboembolectomy was performed. Angiography showed complete recanalization of the left internal carotid artery, ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Decompressive hemicraniectomy is a procedure in which a large bone flap is removed to allow the brain to expand extracranially, alleviating increased intracranial pressure, and has been shown to be a life-saving procedure in the setting of complete middle cerebral artery (MCA) infarction [13][14][15][16]. Following IAT, decompressive hemicraniectomy may be used as emergent management for malignant cerebral edema and/or hemorrhage associated with the infarction [17,18]. It has been suggested that innovations in endovascular techniques may now be decreasing the incidence of hemicraniectomy [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Decompressive hemicraniectomy is a procedure in which a large bone flap is removed to allow the brain to expand extracranially, alleviating increased intracranial pressure, and has been shown to be a life-saving procedure in the setting of complete middle cerebral artery (MCA) infarction [13][14][15][16]. Following IAT, decompressive hemicraniectomy may be used as emergent management for malignant cerebral edema and/or hemorrhage associated with the infarction [17,18]. It has been suggested that innovations in endovascular techniques may now be decreasing the incidence of hemicraniectomy [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%